Indian Architecture in Postcards A New Perspective on a Modern Heritage - Muhidine, Éléonore (Architekturen, 2023)
Focusing on a private collection of 60 postcards of modern architecture in Mumbai, New Delhi, Kolkata, Chennai and Agra, the contributors to this volume explore the many dimensions of modern architecture in India from the 1890s to the 1970s and share their own perspective on these objects. Experts on architectural history and visual studies, as well as postcard collectors provide new insights into a territory and its architectural heritage which is still largely unknown in Europe, and reflect on the postcard as a medium for historical research.